Sphingobium nicotianae sp. nov., isolated from tobacco soil. Issue 4 (6th April 2023) - Fan, Rongrong; Luo, Xiong; Hong, Mengjuan; Yang, Ruijia; Dong, Xinyi; Shi, Heli; Li, Mingshun
Abstract : Bacterial strain H33 T was isolated from tobacco plant soil and was characterized using a polyphasic taxonomy approach. Strain H33 T was a Gram-stain-negative, rod-shaped, non-motile and strictly aerobic bacterium. Phylogenetic analyses based on 16S rRNA gene sequences and coding sequences of the up-to-date bacterial core gene set (92 protein clusters) indicated that H33 T belongs to the genus Sphingobium . Strain H33 T showed the highest 16S rRNA gene sequence similarity to Sphingobium xanthum NL9 T (97.2%) and showed 72.3–80.6 % average nucleotide identity and 19.7–29.2 % digital DNA–DNA hybridization identity with the strains of other species of the genus Sphingobium . Strain H33 T grew optimally at 30°C, pH 7 and could tolerate 0.5 % (w/v) NaCl. The isoprenoid quinones were ubiquinone-9 (64.1%) and ubiquinone-10 (35.9%). Spermidine was the major polyamine. The major fatty acids of H33 T were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ). The polar lipid profile consisted of a mixture of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylmethylethanolamine, sphingoglycolipid, two unidentified lipids, two unidentified glycolipids, two unidentified aminoglycolipids and an unidentified phospholipid. The genomic DNA G+C content of H33 T was 64.9 mol%. Based on the phylogenetic and phenotypic data, H33 T was considered a representative of a novel species in the genus Sphingobium . We propose the name Sphingobium nicotianae sp. nov., with H33 T (=CCTCC AB 2022073 T =LMG 32569 T ) as the type strain.